Gastrointestinal System Adverse Drug Reactions in Geriatric Patients in Odisha - Sahoo, Satyabrata; Dehury, Suhasini; Maharana, Dhirendra Nath; Samajdar, Shambo Samrat (Bengal physician journal, 2023)
Aim and objective: Geriatrics is a specialty that deals with the care of the aged. The term “geriatric population” refers to those over 60 years. In India, the elderly make up 8.14% of the population. The pharmacokinetic and pharmacodynamic aspects of the delivered medications are affected by their complicated physiological and pathological profiles. Polypharmacy can lead to various drug–drug interactions and adverse drug reactions (ADRs) in elderly. Gastrointestinal (GI) system ADRs are mostly found in hospitalized elderly. Gastrointestinal ADRs include upper gastrointestinal bleeding (UGI) bleed, diarrhea, etc.; these are the frequent causes of seriousness and hospitalization in geriatric patients. These ADRs are difficult to manage. To prevent ADRs, we need to understand the risk of potential inappropriate prescribing. Deprescribing in appropriate time can prevent medication-related atrocities. Clinical pharmacological reconciliation and review would help us understand anticholinergic burden associated with polypharmacy. Gastrointestinal system ADRs in geriatric patients have been the subject of a small number of research in India, but none have been undertaken in Odisha. Therefore, the aim of this study is to evaluate the GI ADRs that geriatric patients in Odisha experience. Materials and methods: This prospective, hospital-based observational study was carried out by the SCB Medical College and Hospital's Department of Pharmacology and Geriatric Medicine. From August 2016 to July 2018, all elderly patients (aged ≥60 years) with ADR diagnoses were included. The Suspected Adverse Drug Reaction Reporting Form of Indian Pharmacopoeia Commission Version 1.3 was filled out with the ADRs and their features. The prevalence and profile of GI system ADRs were observed. The WHO-UMC System rated their causation, the Hartwig's Severity Scale evaluated their severity, and the Schumock and Thornton Preventability Scale evaluated their preventability. Results: In 2 years, 236 geriatric ADRs were documented, 11% of which involved the GI system. Out of the GI system ADRs, 85% ADRs were found to be in possible category, 92.3% were found to be of moderate in intensity, and 84.6% were found to be probably preventable. The most frequent GI system ADR identified was UGI bleeding caused by nonsteroidal anti-inflammatory drugs (NSAIDs) (61.5%). Conclusion: Most of the ADRs were found to be of moderate intensity according to Hartwig's Severity Scale and probably preventable according to Schumock and Thornton Preventability scale. NSAID-induced UGI bleeding is the major type of GI system ADR found in this study.